The Use Of Smartphone To Improve Students Reading Comprehension Achievement Of Eighth Grade Students In SMPN 2 Balusu In English Lesson By Online Class - Syahrani Dewi; Ammang Latifa; Badaruddin (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
This study aims to show the students achievement after treated by using smartphone. Based on researcher result observation data through reading comprehension test, the students achievement was place in low classification before giving treatment. It caused of teachers that made students lack of attractive and interest in English learning process. So, the researcher tried to improve students reading comprehension achievement by using smartphone at the eighth grade students of UPTD SMPN 2 Balusu English lesson in online class. The researcher applied pre-experimental with one group pretest and posttest design. The researcher applied these in the eighth grade students with population was 53 students academic year 2020/2021. While, the researcher using purposive sampling technique to determined the sample then, researcher got class VIII/B as a sample which was consisted of 20 students. The result of data analysis presented that the students achievement was improved by used smartphone in learning english process. It was shown of the different between students mean scores in pretest(55,5) and posttest(79,25) while the different scores was 23,75. So, the directed hypothesis was accepted that the students English achievement got much better after they studying English by using smartphone. So, the researcher concluded, smartphone was one of best can improved the students achievement in English learning process at the eighth grade students of UPTD SMPN 2 Balusu.